Giliran Tradition as a Social Practice of Religious Plurality in Kalisat Community, Temanggung, Central Java - Farha, Fina Nayla; Prasetyo, Kuncoro Bayu (Faculty of Social and Political Sciences - UIN Walisongo Semarang, 2023)
The community at Kalisat Hamlet is religiously plural, with the adherents of Buddhism, Islam, Protestantism, Catholicism, and Sapta Dharma living side by side. A social-religious practice called the Giliran tradition has emerged from this plurality—a religious gathering held regularly and simultaneously by all religious groups in Kalisat Hamlet on Saturday nights. This study aims to explain the religious plurality in Kalisat Hamlet, analyze the relationship between the Giliran tradition and the habitus of plurality using Bourdieu’s social practice theory, and analyze the impact of the Giliran tradition on the social order in Kalisat Hamlet. This study uses a descriptive qualitative method with data collected from interviews and field observations. The results show that the plurality in Kalisat Hamlet has produced the Giliran tradition called Paritanan for Buddhists, Yasinan for Muslims, Bestonan for Christians, and Sujudan for Sapta Dharma. The Giliran tradition has also established three basic values—harmony, tolerance, and integration—embedded in the social life of the Kalisat Hamlet community. The values lay a foundation for creating a social order in the Kalisat Hamlet community, which is diverse yet harmonious.